Pemberdayaan Usaha Mikro Kecil dan Menengah (UMKM) dalam Penanggulangan Kemiskinan - Ferry Duwi Kurniawan; Luluk Fauziah (Universitas Muhammadiyah Sidoarjo, 2014)
The purpose of this study to analyze and describe the empowerment of small and Medium Enterprises (SMEs) as reduction of poverty in Waru Rejovillage, Gempol Subdistrict, Pasuruan Regency as well as describe its supporting and inhibiting factors. This study used descriptive qualitative method. Data was collected through observation, interviews and documentation. The results of this study indicated the process of empowerment has been done by the government was limited to the provision of capital to develop Small and Medium Enterprises. In this empowerment, there are supporting factors included sufficient of labor, raw materials were cheap and easy to find, law of capital, the support from apparatus village, supply raw materials were easy, agreement of selling price between group members. Meanwhile, inhibiting factor in this empowerment were inadequate or damaged on infrastructure, minimum assistance from the government, lack of waste disposal sites, and nothing of marketing products.